Personality differences and buyer-supplier relationships: Psychopathy in executives, gender differences and implications for future research. Issue 4 (October 2021) - Croom, Simon; Fritzon, Katarina; Brooks, Nathan
Abstract: The buyer-supplier relationships (BSRs) literature to date has neglected the implications of individual personality differences amongst the parties to any relationship, thereby ignoring the complex dynamics of human interaction and behaviors on the progress and performance in such relationships. This Notes & Debates paper takes the view that personality matters, particularly toxic personality traits, and argues that for purchasing & supply researchers a cross-disciplinary approach to the study of BSRs will advance our understanding. Our study brought together psychology and supply management researchers. We begin by arguing that much of the extant literature demotes behavior and personality to peripheral, exogenous, or even irrelevant to the study of BSRs. Second, by focusing on the emergent research into corporate psychopathy, we explore one specific aspect of individual personality differences – psychopathic personality disorder. Third, we present our findings from a study of psychopathy in two executive samples, one consisting of exclusively procurement executives, to illustrate some of the personality traits likely to prevail within BSRs. Key to our argument, we found significant individual differences across our samples. Indeed, the incidence of psychopathic traits was higher than reported in the few prior studies of corporate psychopathy. We also found significant gender differences, marked not only by slightly higher levels of psychopathy in males than females, but by differences in the disposition of psychopathy. We also found that the relationship between psychopathy and seniority was significant, indicative of a relationship between executive status and potentially toxic behaviors. Future studies of BSRs thus need to recognize and account for individual differences in BSRs; such differences are not inconsequential. Highlights: Current research into Buyer-Seller Relations has largely excluded examination of personality differences. Analysis of personality differences in an executive sample found high incidence of psychopathic personality traits. Gender differences in psychopathy were marked by differences in its manifestation between males and females. Future research into personality and individual differences is discussed.